Television and movies as instructional aids for values development among Assumption high schools and partner schools in the Philippines - Hechanova, Maria Nilda P. (Animo Repository, 2005)
This study designed five modules using television and movies as instructional aids to develop the values of fairness, honesty, self-discipline, and social responsibility for Assumption High Schools and partner schools in the Philippines. The modules took off from the results of the three surveys to gather the participants television viewing habits, practices, and interests; their perceptions on violence and sex in TV programs, and truth/falsity in advertisements; and their values development index. The study covered a random cluster sample of 265 first year high school students from three Assumption schools located in the urban area and three partner schools located in the rural area. Using Tylers model for instructional planning and Kohlbergs theoretical framework for moral development, value dilemmas were drawn from television programs and movies and discussed: a TV drama, Anak; a movie, Erin Brokovich; a serial, Endless Love; and a cartoon, Mulan. The modules were implemented and evaluated using an experimental approach involving a random sample of 126 participants who composed the experimental and control groups coming from an Assumption school in the urban area and a partner school in the rural area. The study yielded the following significant results, tested at a: .05, two tailed: (1) There was a relationship between the participants viewing habits, practices and interests and their: (a) school location (rural/urban), (b) gender (male/female), and (c) school attended (Assumption/partner school); (2) There was a relationship between the participants perceptions on violence in TV programs and their: (a) school location, except in one item; (b) gender, except in four items; and (c) school attended, except in two items; (3) There was a relationship between the participants perceptions on sex in 2 TV programs and their: (a) school location, except in two items; (b) gender, except in six items; and (c) school attended, except in three items; (4) There was a relationship between the participants perceptions on truth/falsity in advertisements and their: (a) school location, except in five items; and (b) school attended, except in four items. There was no relationship between the participants perceptions on truth/falsity in advertisements and their gender. There were ten items in each category; (5) There was a relationship between the participants values development index and their: (a) school location, (b) gender, and (c) school attended; and (6) The five modules using television and movies as instructional aids to develop the values of fairness, honesty, self discipline, and social responsibility were effective among the first year high school students in a partner school and partially effective in an Assumption school in the Philippines. The study recommends the use of television and movies as instructional aids for values development. This implies a training of teachers especially on how to use these materials using Kohlbergs paradigm for values development. Considering the role of the family in values development, it is recommended that parents be given relevant information and formation on media education and values development. It is also recommended that the TV industry be encouraged, challenged, and supported to come up with programs that are value-laden to strengthen family life and help in nation building.